CAROLINE FRICK, Saving Cinema: The Politics of Preservation - Cannon, Braden (Archivaria, 2012)
Saving Cinema: The Politics of Preservation. CAROLINE FRICK. Oxford: Oxford University Press, 2011. xiii, 215 p. ISBN 978-0-19-536811-6